Retrospective cohort study for thrombocytopenia during concurrent chemoradiotherapy for rectal cancer - Yue Teng; Dapeng Ma; Yan Yan; Jianhao Geng; Zhiyan Liu; Xianggao Zhu; Shuai Li; Yangzi Zhang; Hongzhi Wang; Yong Cai; Haizhen Yue; Yongheng Li; et al. (Frontiers in Oncology, 2024)
BackgroundThe aim of this article was to establish the clinical prognostic models and identify the predictive radiation dosimetric parameters for thrombocytopenia during concurrent chemoradiotherapy for rectal cancer.MethodsIn this retrospective cohort study, patients with rectal adenocarcinoma undergoing concurrent long-term chemoradiotherapy were included. The primary outcome of interest was grade 2 or higher (2+) thrombocytopenia (platelet(PLT) count <75,000/μL). Secondary outcomes included: grade 1 or higher thrombocytopenia (PLT count<100,000/μL) and the PLT count during chemoradiotherapy and its nadir. The risk prediction model was developed by logistic regression to identify clinical predictors of 2+ thrombocytopenia. Univariate linear regression models were used to test correlations between radiation dosimetric parameters and the absolute PLT count at nadirs.ResultsThis retrospective cohort comprised 238 patients. Fifty-four (22.6%) patients developed thrombocytopenia during concurrent chemoradiotherapy, while 15 (6.3%) patients developed 2+ thrombocytopenia. Four independently associated risk factors, including age, Alb level, PLT count, and chemotherapy regimen, were included in the final model and used to form a 2+ thrombocytopenia probability estimation nomogram. The C‐index was 0.87 (95% CI: 0.78–0.96). The calibration plot showed a moderate agreement, and the Brier score was 0.047 (95% CI: 0.025–0.070). The total absolute volume of bone marrow irradiated by 5 Gy, 10 Gy and 15 Gy of radiation (BM-V5ab, BM-V10ab, BM-V15ab), calculated by the volume of bone marrow multiplied by the corresponding Vx, were identified as new predictors. The nadir of PLT was found to be negatively correlated with BM-V5ab (β = -0.062, P =0.030), BM-V10ab (β = -0.065, P =0.030) and BM-V15ab (β = -0.064, P =0.042).ConclusionThe occurrence of 2+ thrombocytopenia during concurrent chemoradiotherapy for rectal cancer can be predicted by the patient’s baseline status and chemoradiotherapy regimen, and low dose irradiation of bone marrow can affect the level of platelets during the treatment.